Tuberculosis Case Finding Cascade and Treatment Outcomes among Male Inmates in Two Prisons in Zimbabwe. (9th July 2020) - Mandizvidza, Alois; Dlodlo, Riitta A.; Chinnakali, Palanivel; Mugauri, Hamufare Dumisani; Dube, Freeman; Gaka, Evidence; Nembaware, Joseph; Nyambi, Shepherd; Masunungure, Blessing; Garauzive, Davison
Abstract : Setting . Zimbabwe is a high tuberculosis (TB) burden country, with an estimated prevalence of 344/100, 000 population. Though prisons are known high-prevalence sites for TB, the paucity of data affects the quantification of the disease and treatment outcomes in these settings. We measured the prevalence of TB disease and treatment outcomes among inmates at two major prisons in Harare, Zimbabwe. Design . A cohort study using programmatic data was undertaken to assess TB diagnostic cascade in one of the study prisons for 2018. Treatment outcomes among male inmates with TB were assessed over a period of four years, in two study prisons. Results . A total of 405 (11%) inmates with presumptive TB were identified, and 370 (91%) of these were evaluated for TB, mostly using rapid molecular testing of sputum specimens. Twenty-five inmates were diagnosed with TB resulting in a prevalence of 649/100, 000 population. Of these, 16 (64%) were started on treatment. Nine (36%) were lost to follow-up before treatment initiation. From 2015 to 2018, 280 adult male inmates with TB were started on treatment. Of these, 212 (76%) had pulmonary disease that was bacteriologically confirmed. Almost all (276/280, 99%) had known HIV status, 65% were HIV-infected, and 80% of these were on antiretroviral treatment. The TB treatment success rate (cured or treatment completed) was recorded for 209 (75%) inmates, whilst 14 (5%) died and 11 (4%) were lost to follow-up. The frequency of unfavourable treatment outcomes (death, lost to follow-up, and not evaluated) was higher (54%) among inmates ≥ 60 years than those in the age group of 45-59 years (17%). Conclusion . The findings revealed a threefold burden of TB in prisons, compared with what is reported by national survey. To decrease transmission of TB bacilli, it is essential to promote efforts that address missed opportunities in the TB diagnostic cascade, prompt treatment initiation, and ensure that tracking and documentation of treatment outcomes for all inmates are intensified.